On the Eve of Independence: The Ecological Situation in Uzbekistan and its Impact on Human Health (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article discusses the ecological situation in Uzbekistan on the eve of gaining independence and its impact on human health. The article also analyzes, based on concrete evidence, the regions in the republic where the ecological environment has deteriorated and the reasons behind this situation.